Association of protein tyrosine phosphatase 1B gene polymorphisms with measures of glucose homeostasis in Hispanic Americans: The Insulin Resistance atherosclerosis Study (IRAS) Family Study - PALMER, Nicholette D; BENTO, Jennifer L; MYCHALECKYJ, Josyf C; LANGEFELD, Carl D; CAMPBELL, Joel K; NORRIS, Jill M; HAFFNER, Stephen M; BERGMAN, Richard N; BOWDEN, Donald W (Diabetes (New York, N.Y.), 2004)
Protein tyrosine phosphatase (PTP)-1B, encoded by the PTPN1 gene, catalyzes the dephosphorylation of proteins at tyrosyl residues. PTP-1B has been implicated in negatively regulating insulin signaling by dephosphorylating the phosphotyrosine residues of the insulin receptor. The genetic contribution of PTPN1 to measures of glucose homeostasis has been assessed in 811 Hispanic subjects from the Insulin Resistance Atherosclerosis Study Family Study (IRASFS). Thirty-five single nucleotide polymorphisms (SNPs) spanning 161 kb and containing the PTPN1 gene were genotyped and tested for association. All 20 SNPs with minor allele frequencies >0.1 in a single haplotype block covering the PTPN1 genomic sequence show significant association with the insulin sensitivity index (S(i)) (P = 0.044-0.003) and fasting glucose (P = 0.029 to <0.001). In contrast, there is no evidence for association of PTPN1 polymorphisms with acute insulin response (a measure of beta-cell function). Haplotype analysis of eight SNP haplotypes that have independently been shown to be associated with type 2 diabetes risk and protection in Caucasian type 2 diabetic subjects are associated with lower (P = 0.007) and higher (P = 0.0002) S(i) and higher (P = 0.00007) and lower (P = 0.001) fasting glucose, respectively, in the IRASFS. This comprehensive genetic analysis of PTPN1 reveals significant association with metabolic traits consistent with the proposed in vivo role for the PTP-1B protein.